2008
DOI: 10.1007/s00414-008-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Null allele sequence structure at the DYS448 locus and implications for profile interpretation

Abstract: Null alleles can occur with any PCR-based STR typing system. They generally are due to deletions within the target region or primer binding sites or by primer binding site mutations that destabilize hybridization of at least one of the primers flanking the target region. Although not common, null types were detected at the DYS448 locus in seven out of 1,005 unrelated males in the Hispanic population. Of these DYS448 null types, four individuals displayed an apparent duplication at the DYS437 locus. The additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
5
16
1
Order By: Relevance
“…The sample was analysed in triplicate by both systems, and the results were the same. Similar discordances reported in other studies have proved to be due to mutations which probably coincided with the 3′ end binding region of one of the primers [30,31].…”
Section: Preliminary Concordance Studiessupporting
confidence: 67%
“…The sample was analysed in triplicate by both systems, and the results were the same. Similar discordances reported in other studies have proved to be due to mutations which probably coincided with the 3′ end binding region of one of the primers [30,31].…”
Section: Preliminary Concordance Studiessupporting
confidence: 67%
“…A concordance of 99.9% between the genetic profiles of the two components of the kit I-DNADuo was observed, a result similar to those of other concordance studies [8,9]. Previous studies have reported that these discordances were due to mutations which probably coincide with the 3′ end binding region of one of the primer pairs, so the combination of two kits with different primers is therefore of great interest in detecting and preventing allelic dropouts [10][11][12].…”
Section: Preliminary Concordance Studiessupporting
confidence: 87%
“…Null alleles at the locus DYS448 have been reported previously, with relatively high frequencies in Asians [20][21][22]. Null alleles can occur due to primer binding sites mutations or sequence deletions within the STR regions or primer binding regions [20]. Since different method might use different primers, it seems that some deletions may occur within the detected regions of DYS448 locus, which results in amplification failures of all the primer pairs [23].…”
Section: Resultsmentioning
confidence: 93%
“…These two samples were then typed with the Yfiler ® Plus PCR Amplification Kit (Thermo Fisher) and the AGCU Database Y24 Fluorescence Detection Kit (AGCU), and similar dropout phenomena were observed. Null alleles at the locus DYS448 have been reported previously, with relatively high frequencies in Asians [20][21][22]. Null alleles can occur due to primer binding sites mutations or sequence deletions within the STR regions or primer binding regions [20].…”
Section: Resultsmentioning
confidence: 94%